ADAPTOR MESIN PENCACAH SAMPAH PLASTIK - Zahwa, Muh Adam; Hamka, Muhammad; Alamuddin, Yusuf; Hermansyah, Hermansyah; Gunawan, Randi; Akil, Ahmad; Hasnah, Nur; Najamuddin, Husnul Khatimah; Ulfayani, Ulfayani; Alamudi, Kalsum (Universitas Muhammadiyah Tangerang, 2021)
Plastic waste is a material that is difficult to decompose when buried in the ground. The large amount of plastic waste from human activities can cause environmental pollution. The reason for designing this plastic trash chopper is because the price of machines that have been marketed has an expensive price. Prices on the market range from around Rp. 18.000.000 to Rp. 30.000.000 depending on the engine specifications. In addition to the price of the machine i tu own, reasons that become the background count tool design plastic waste is due to concerns about trash, especially plastic waste in the city of Palembang, which until now still cannot be solved by optimal. To overcome these problems, a redesign of a plastic trash chopper was carried out using the Value Engineering method. From the results of research and analysis is known that p e designof the machine counter trash plastic the profit that as many as 8 benefit with b iaya value of VE were issued at 5.44. The total costs incurred after the redesign was carried out, amounting to Rp.1.470 .000.